The Production of the 'Uberabão' Stadium: Interests, Uses, and Appropriations in the Context of the Development of Football in Uberaba (Élisée - Revista de Geografia da UEG, 2024)
Football is one of the greatest cultural and sporting expressions in Brazil and its existence is not limited to the four lines where a match takes place. The football stadium supports leisure and spectacle. This paper analyzes, in historical perspective, the production process, the uses and functions of Engenheiro João Guido Municipal Stadium, the Uberabão, and its impacts on the urban space of Uberaba-MG. It highlights the public and private interests on this equipment as well as their influences on the organization and territorial appropriation in its surroundings. Based on specific bibliography, historical data survey in public agencies, analysis of photographs and aerial images and field visits, the work demonstrated the stadium project linked to the interests of local elites, to the city's attempt of projection in the regional and national sports circuit as well as to the attempt to implement a large-scale urban equipment that could support urban expansion in the area where it is located, aggregating different land uses and occupations.
Keywords: Urban geography; urban space; production of urban space; football stadium; Uberaba.